2018
DOI: 10.1186/s12967-018-1583-7
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates spinal cord ischemia–reperfusion injury through both anti-inflammation and anti-apoptosis mechanisms in rabbits

Abstract: BackgroundDexmedetomidine (Dex) can improve neuronal viability and protect the spinal cord from ischemia–reperfusion (I/R) injury, but the underlying mechanisms are not fully understood. This study investigated the effects of dexmedetomidine on the toll-like receptor 4 (TLR4)-mediated nuclear factor κB (NF-κB) inflammatory system and caspase-3 dependent apoptosis induced by spinal cord ischemia–reperfusion injury.MethodsTwenty-four rabbits were divided into three groups: I/R, Dex (10 µg/kg/h prior to ischemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…[8][9][10] Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist with sedative, anxiolytic, analgesic, and sympatholytic properties. 11,12 Our previous studies showed that DEX use was associated with improved outcomes and reduced mortality in patients undergoing cardiac surgery. 13,14 In a rat myocardial I/R model, DEX administration prior to ischemia (pretreatment) reduced the myocardial infarct size by inhibiting inflammation via the α2-adrenergic receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist with sedative, anxiolytic, analgesic, and sympatholytic properties. 11,12 Our previous studies showed that DEX use was associated with improved outcomes and reduced mortality in patients undergoing cardiac surgery. 13,14 In a rat myocardial I/R model, DEX administration prior to ischemia (pretreatment) reduced the myocardial infarct size by inhibiting inflammation via the α2-adrenergic receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromotor function of rats is an important criterion for observing SCI and its recovery . Sensory and functional recovery is the most important and direct observation index for SCI treatment . BBB scores and inclined plate tests were used to assess the severity of SCI.…”
Section: Resultsmentioning
confidence: 99%
“…31 Sensory and functional recovery is the most important and direct observation index for SCI treatment. 8 BBB scores and inclined plate tests were used to assess the severity of SCI. The results showed that compared with the SCI group, the BBB score and inclined plate test score of the SCI-RHL group increased significantly F I G U R E 2 RHL improved antioxidant activity in spinal cord tissues after SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations